Pengaruh Online Customer Review, Customer Rating Dan Harga Terhadap Minat Beli Konsumen Di Tokopedia - Ainur Rasyid; Muhammad Ridwan Basalamah; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine the extent to which Online Customer Reviews, Customer Ratings, and Prices influence the Buying Interest of Tokopedia consumers. The population in this study were 565 students of the Faculty of Economics and Business at the Islamic University of Malang and the sample used in this study used the slovin approach so that a sample of 85 was obtained. The test was carried out using IBM SPSS version 25. The results obtained were online Customer Reviews, Customer Ratings and Prices had a positive effect and simultaneously significant to buying interest in Tokopedia. Meanwhile, partially Online Customer Reviews have a positive and significant effect on purchase intention at Tokopedia, Customer Ratings have a positive and significant effect on purchase intention at Tokopedia, Prices have a positive and significant effect on purchase intention at Tokopedia. Keywords: Purchase intentio, Online Customer Review, rating and Price.